Phenothiazine dyes containing a 4-phenyl-2-(thiophen-2-yl) thiazole bridge for dye-sensitized solar cells. Issue 15 (10th April 2020) - Han, Liang; Chen, Yaqian; Zhao, Jin'ge; Cui, Yanhong; Jiang, Shaoliang
Abstract: Two novel phenothiazine dyes bearing a single or double cyanoacrylic acid acceptors, which share the same electron donor phenothiazine and the same 4-phenyl-2-(thiophen-2-yl)thiazole π-bridge, were synthesized. Thus, phenothiazine dyes with D-π-A and A-D-π-A framework were configured, and their photophysical properties and photovoltaic performance were investigated. The incorporation of another cyanoacrylic acid acceptor was found to benefit the loading amount on TiO2, the light-harvesting ability, and the electron-injection efficiency. Dye with double cyanoacrylic acid acceptors showed a double short-circuit current compared with dye with a single acceptor. Therefore, dye with double cyanoacrylic acid acceptors achieved improved photoelectric conversion efficiency 4.35% ( J SC  = 10.29 mA cm −2, V OC  = 0.65 V, FF = 0.65) under standard global AM 1.5 G solar condition with dye N719 (7.19%) as a reference. Graphical abstract: Image 1 Highlights: Two novel phenothiazine dyes have been synthesized with a single or double cyanoacrylic acid acceptors. The incorporation of another cyanoacrylic acid acceptor was observed to be beneficial to the photovoltaic performance. Dye with double acceptors shows better photoelectric conversion efficiency than dye with a single acceptor.